PENGARUH FINANCIAL TECHNOLOGY, FINANCIAL KNOWLEDGE DAN FINANCIAL ATTITUTE TERHADAP FINANCIAL MANAGEMENT BEHAVIOUR MAHASISWA - Ciptaningtias, Arum Febriyanti; Astungkara, Agni; Mahesti, Triloka (Jurnal Akuntansi dan Pajak, 2024)
The development of financial technology can change the way people conduct financial transactions and quickly convert cash transactions to cashless. This research aims to determine the effect of financial technology, financial knowledge, and financial attitude on bachelor students' financial management behavior. The research methodology used is a quantitative approach, utilizing primary data obtained from 88 questionnaire answers. Data were analyzed using descriptive statistical analysis, instrument test, normality test, multiple regression analysis, and hypothesis testing. The test was assisted by SPSS 22 software. The results show that financial knowledge and financial attitude affect financial management behavior partially. Meanwhile, financial technology has no effect toward financial management behavior partially. Keywords: Financial Technology, Financial Knowledge, Financial Attitude, Financial Management Behaviour